Administrative System and Procedures for Non-Capitation Fund Claims at The Social Security Administration Agency (BPJS) Health Branch Serang - Indah Rahayu (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to identify the procedures or administrative requirements for non-capitation claims at the BPJS Health Branch Serang. The research method used to address the research question is descriptive method. The data sources used are primary data and secondary data. The primary data collected for this final project report is the result of interviews with the employees. The secondary data is obtained by utilizing processed data owned by my internship site, which is the Social Health Insurance Provider Agency (BPJS) Health Main Branch Serang. The research findings show that the administration of non-capitation claims at the BPJS Health Main Branch Serang is well-structured and organized.